2011
DOI: 10.1021/es103365b
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Sensitive Detection Method for Stressed E. coli O157:H7 in Source and Finished Drinking Water by Culture-qPCR

Abstract: A sensitive and specific method that also demonstrates viability is of interest for detection of E. coli O157:H7 in drinking water. A combination of culture and qPCR was investigated. Two triplex qPCRs, one from a commercial source and another designed for this study were optimized from 5 different assays to be run on a single qPCR plate. The qPCR assays were specific for 33 E. coli O157:H7 strains tested and detected 500 cells spiked in a background of 10(8) nontarget bacterial cells. The qPCR detection was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Enrichment of bacteria in a growth medium prior to qPCR has been used in several publications, e.g. for measuring viability of Escherichia coli O157:H7 in drinking water [12]. When the measured Ct values are lower than what can be expected from the residual DNA used for inoculating the media it can be concluded that this must be dependent on the growth of the bacterium in the enrichment medium.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of bacteria in a growth medium prior to qPCR has been used in several publications, e.g. for measuring viability of Escherichia coli O157:H7 in drinking water [12]. When the measured Ct values are lower than what can be expected from the residual DNA used for inoculating the media it can be concluded that this must be dependent on the growth of the bacterium in the enrichment medium.…”
Section: Discussionmentioning
confidence: 99%
“…Exponential phase in qPCR technique can be continuously observed for 30-50 Cqs and can be used to estimate the initial number of targeted DNA. The use of a qPCR assay to positively detect E. coli O157:H7 strains in drinking water was carried out using molecular beacons (MBs) oligonucleotide probes [119], InstaGene TM matrix from Bio-Rad specially formulated 6% w/v Chelex resin [120], minor groove binding (MGB) probes with 6-FAM (6-carboxyfluorescein) [121] and propidium monoazide (PMA-based) qPCR assay [122]. Quantitative PCR assay provides the possibility of quantitative analysis for E. coli target by using formulated structural quantification curve as shown in Fig.…”
Section: Dna/rna Amplificationmentioning
confidence: 99%
“…A combined culture-qPCR method specific for detection of E. coli O157:H7, a potentially lethal strain of EHEC implicated in waterborne outbreaks of hemorrhagic colitis and hemolytic-uremic syndrome, has been described (Sen et al, 2011). In this method, concentrated presence-absence broth (Remel Inc., Lenexa, KS, USA) was added to a 1-l water sample to enrich for O157:H7.…”
Section: Pathogenic Escherichia Colimentioning
confidence: 99%